2009
DOI: 10.1590/s1984-82502009000300009
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity of extracts and isolated compounds from Stryphnodendron obovatum Benth

Abstract: The extract from stem bark of Stryphnodendron obovatum Benth. was chromatographed on a Sephadex ® LH-20 column, and yielded nine compounds: gallic acid (GA), p-hydroxybenzoic acid (PHB), gallocatechin (GC), epigallocatechin (EPG), 4'-O-methylgallocatechin (MGC), epigallocatechin-(4b→8)-epigallocatechin (EPEP), epigallocatechin-(4b→8)-gallocatechin (EPGC), robinetinidol-(4a→8)-gallocatechin (ROGC) and robinetinidol-(4b→8)-epigallocatechin (ROEP). Evaluation of the antioxidant capacity in vitro by the methods of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
(37 reference statements)
0
7
0
1
Order By: Relevance
“…S. coriaceum exhibits acetylcholinesterase inhibitory activity, as well as antioxidant, anti-inflammatory, antimicrobial, healing, antiulcerogenic, and leishmanicidal activities [ 35 , 36 ]. The S. coriaceum extract was shown to have excellent acetylcholinesterase inhibitory and antioxidant activities, which make it another potential source of therapeutic agents against AD.…”
Section: Resultsmentioning
confidence: 99%
“…S. coriaceum exhibits acetylcholinesterase inhibitory activity, as well as antioxidant, anti-inflammatory, antimicrobial, healing, antiulcerogenic, and leishmanicidal activities [ 35 , 36 ]. The S. coriaceum extract was shown to have excellent acetylcholinesterase inhibitory and antioxidant activities, which make it another potential source of therapeutic agents against AD.…”
Section: Resultsmentioning
confidence: 99%
“…Zocoler et al [65] demonstrated a strong relationship between anti-inflammatory activity of the Stryphnodedron obovatum with the presence of gallic acid, epigallocatechin, and gallocatechin. Araújo-Neto et al [66] have shown the anti-inflammatory effect of tannins and flavonoids in studies with Sideroxylon obtusifolium on paw edema induced by carrageenan and peritoneal leukocyte infiltrate in rats.…”
Section: Resultsmentioning
confidence: 99%
“…Among such phenols, the most common have been gallic acid, p-hydroxybenzoic acid, catechin derivatives and tannins isolated from acetone : water (7 : 3 v/v) and ethyl acetate extracts. 2,7,8 Numerous experimental and epidemiological studies have also shown that phenolics, avonoids and catechin derivatives are commonly found in Stryphnodendron spp, and these constituents are normally described as antioxidants. 9,10 Polyphenols and derivatives in plant extracts have been determined mainly via chromatographic protocols, but more recently direct infusion electrospray ionization mass spectrometry (ESI-MS) has been increasingly used to obtain proles of phenolic compounds from plant extracts, particularly when the elemental composition can be inferred from the MS measurements.…”
Section: Introductionmentioning
confidence: 99%